2005
DOI: 10.1093/jmedent/42.4.702
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Human Myiasis Caused by Chrysomya megacephala and Chrysomya rufifacies (Diptera: Calliphoridae) in Thailand, and Its Implication in Forensic Entomology

Abstract: We report a forensic entomology case associated with human myiasis in Chiang Mai Province, northern Thailand. The remains of a 53-yr-old-male were concurrently infested with third instars of the two blow fly species, Chrysomya megacephala (F.) and Chrysomya rufifacies (Macquart), near a severe tumor lesion presented on the lower right leg. The presence of third instars, approximately 5 d old, on the day following postmortem indicated that myiasis occurred before death. This is the first report of both fly spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 4 publications
3
30
0
Order By: Relevance
“…Diptera constitute along with Coleoptera the majority of the necrophage insects representing the largest portion of cadaveric fauna found on carcasses during the decomposition process [43][44][45] and that was also observed in this study. For this reason, members of Sarcophagidae, Calliphoridae and Muscidae family have been commonly cited in forensic entomology studies [46,47] as observed in this study as well.…”
Section: Discussionsupporting
confidence: 71%
“…Diptera constitute along with Coleoptera the majority of the necrophage insects representing the largest portion of cadaveric fauna found on carcasses during the decomposition process [43][44][45] and that was also observed in this study. For this reason, members of Sarcophagidae, Calliphoridae and Muscidae family have been commonly cited in forensic entomology studies [46,47] as observed in this study as well.…”
Section: Discussionsupporting
confidence: 71%
“…It was introduced into southern Brazil in the 1970s and today has been distributed widely throughout the Neotropical region (Guimarães et al, 1978;Prado and Guimarães, 1982). This fly is important because of its high natural population densities, high degrees of synanthopy and endophily, its potential to produce secondary myiasis in humans and other animals, and its use as a forensic indicator (James, 1947;Greenberg, 1971;Guimarães and Papavero, 1999;Oliveira-Costa and Mello-Patiu, 2004;Carvalho et al, 2004;Sukontason et al, 2005;Carvalho and Von Zuben, 2006). Because C. megacephala feeds and breeds easily in human and animal feces, carrion, foodstuffs, liver and fish (Laurence, 1981;Baumgartner and Greenberg, 1984;d'Almeida, 1993), it is a potential mechanical vector of viruses, bacteria and other enteropathogenic organisms (Greenberg, 1971;1973;Guimarães et al, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Its negative impact plays an important role in being a nuisance and mechanical carrier of pathogens and causing myiasis [e.g. [36][37][38][39][40][41][42][43][44][45]. On the other hand, it is beneficial when applied in debridement therapy [46] and forensic entomology [47].…”
Section: Medically-important Aspects Of the Blow Fly: Thailand Appraisalmentioning
confidence: 99%
“…Many species of Diptera may cause larval infestation or infection in humans [49]. Blow fly maggots have been recognized as myiasis producers worldwide, in several countries such as Brazil [50][51], India [44], Thailand [41,[52][53] and Sri Lanka [54]. Human myiasis in Thailand is an uncommon parasitic infestation.…”
Section: Medically-important Aspects Of the Blow Fly: Thailand Appraisalmentioning
confidence: 99%